Performance evaluation of highly conductive graphene (RGOHI–AcOH) and graphene/metal nanoparticle composites (RGO/Ni) coated on carbon cloth for supercapacitor applications. Issue 113 (30th October 2015) - Valipour, Alireza; Hamnabard, Nazanin; Ahn, Young-Ho
Abstract : The application of graphene (RGO)-based composites as electrode materials in supercapacitors can be limited by the fabrication complexity and costs, and the non-environmentally friendly nature of the production process. Abstract : The application of graphene (RGO)-based composites as electrode materials in supercapacitors can be limited by the fabrication complexity and costs, and the non-environmentally friendly nature of the production process. This study examined the effectiveness of a highly conductive graphene material (RGOHI–AcOH ) compared to the hydrazine-produced RGO and graphene nanoparticle composite (RGO/Ni) materials on a carbon cloth substrate in supercapacitors. The composites were synthesized at different mass ratios (1 : 1, 2 : 1, 4 : 1, 10 : 1 and 1 : 2) of RGO to Ni nanoparticles. All synthesized samples were characterized using X-ray diffraction, scanning electron microscopy, atomic force microscopy, X-ray photoelectron spectroscopy and Raman spectroscopy. The methylene blue method was used for determining the specific surface area. The RGOHI–AcOH electrode exhibited a higher electrochemical performance (40 F g −1 at 10 mV s −1 and 70 F g −1 at 0.2 A g −1 ) and stability (∼94%) than the other electrodes examined. Among the prepared composites, the composite with a RGO to Ni nanoparticle mass ratio of 1 : 1 showed a better electrochemical performance (30 F g −1 at 10 mV s −1, and 27 F g −1 at 0.2 A g −1 ) than the hydrazine-produced RGO and the other composite electrodes. Overall, RGOHI–AcOH as a first priority electrode material (particularly, coated on a carbon cloth substrate) has potential applications in energy storage devices.